The Art of the Start 2.0 : The Time-Tested, Battle-Hardened Guide for Anyone Starting Anything - Kawasaki, Guy (New York Portfolio/Penguin, 2015)
Newly revised and updated, a 10th-anniversary edition of an iconic, best-selling guide for start-ups provides expert advice on a wealth of topics -- including writing a business plan, recruiting, raising capital and branding. --Publisher's description.
Include Illustrations, Tables and Index
Keywords: New business enterprises -- Entrepreneurship